2021
DOI: 10.3390/nu13020499
|View full text |Cite
|
Sign up to set email alerts
|

Does the High Prevalence of Vitamin D Deficiency in African Americans Contribute to Health Disparities?

Abstract: African Americans have higher incidence of, and mortality from, many health-related problems than European Americans. They also have a 15 to 20-fold higher prevalence of severe vitamin D deficiency. Here we summarize evidence that: (i) this health disparity is partly due to insufficient vitamin D production, caused by melanin in the skin blocking the UVB solar radiation necessary for its synthesis; (ii) the vitamin D insufficiency is exacerbated at high latitudes because of the combination of dark skin color w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
100
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(103 citation statements)
references
References 179 publications
(225 reference statements)
1
100
1
1
Order By: Relevance
“…Neighborhood physical disorder is a condition often cited in bio-psychosocial models that links societal and systemic stressors to chronic inflammation which can drive immune dysregulation and poor health outcomes amongst disadvantaged communities ( 20 ). Additionally, researchers have also considered the disproportionate rates of vitamin D deficiency amongst African Americans as another potential contributor to healthcare disparities and sub-optimal immune function in this population ( 21 ). Put simply, we feel it is important to identify the potential differences in cancer biology amongst racial groups because it could be useful in the application of IO therapy in minority populations with oncologic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Neighborhood physical disorder is a condition often cited in bio-psychosocial models that links societal and systemic stressors to chronic inflammation which can drive immune dysregulation and poor health outcomes amongst disadvantaged communities ( 20 ). Additionally, researchers have also considered the disproportionate rates of vitamin D deficiency amongst African Americans as another potential contributor to healthcare disparities and sub-optimal immune function in this population ( 21 ). Put simply, we feel it is important to identify the potential differences in cancer biology amongst racial groups because it could be useful in the application of IO therapy in minority populations with oncologic disease.…”
Section: Discussionmentioning
confidence: 99%
“…122,123 Moreover, in controlled clinical trials, vitamin D administration has shown a protective effect against respiratory infections in healthy patients as well as in patients with chronic obstructive pulmonary disease and other related pathologies, including COVID-19. 124 Nonetheless, additional studies are imperative to gain a better understanding of the interaction of vitamin D with ACE2 and its role in COVID-19.…”
Section: Vitamin D and Ace2mentioning
confidence: 99%
“…A combined analysis of two randomized controlled trials by Ames et al revealed that supplementing vitamin D ranging from 2400 IU/d to 4000 IU/d led to a reduction in the likelihood to have asthma flare-ups from zero to three years by 24% [adjusted odds ratio (aOR): 0.74, 95% CI = 0.57 to 0.96); participants with a basal level of greater than or equal to 30ng/ml 25(OH)D (aOR:0.54, 95% CI = 0.33 to 0.88) [20]. Ames et al also found that supplementing 4000 IU/d vitamin D in a randomized controlled trial led to a similar increase in vitamin D levels for both African Americans and non-African Americans, while a metanalysis of individuals from seven randomized controlled trials with high-quality evidence also revealed a reduction in asthma exacerbation requiring systemic corticosteroids after taking vitamin D supplements by 26%.…”
Section: Effect Of Vitamin D Supplementation On Asthma Exacerbation In Adultsmentioning
confidence: 99%